COMPARATIVE STUDY OF WING LIFT DISTRIBUTION ANALYSIS USING NUMERICAL METHOD - Septiyana, Angga; Hidayat, Kurnia; Rizaldi, Ardian; Wijaya, Yusuf Giri (Indonesian Journal of Aerospace, 2020)
This research focuses on calculating the force distribution on the wings of the LSU 05-NG aircraft by several numerical methods. Analysis of the force distribution on the wing is important because the wing has a very important role in producing sufficient lift for the aircraft. The numerical methods used to calculate the lift force distribution on the wings are Computational Flow Dynamics (CFD), Lifting Line Theory, Vortex Lattice Method and 3D Panel Method. The numerical methods used will be compared with each other to determine the accuracy and time required to calculate wing lift distribution. Because CFDs produce more accurate estimates, CFD is used as the main comparison for the other three numerical methods. Based on calculations performed, 3D Panel Method has an accuracy that is close to CFD with a shorter time. 3D Panel Method requires 400 while CFD 1210 seconds with results that are not much different. While LLT and VLM have poor accuracy, however, shorter time is needed. Therefore to analyze the distribution of lift force on the wing it is enough to use the 3D Panel Method due to accurate results and shorter computing time.